Peculiar genomic traits in the stress-adapted cryptoendolithic Antarctic fungus Friedmanniomyces endolithicus. Issue 5 (May 2020) - Coleine, Claudia; Masonjones, Sawyer; Sterflinger, Katja; Onofri, Silvano; Selbmann, Laura; Stajich, Jason E.
Abstract: Friedmanniomyces endolithicus is a highly melanized fungus endemic to the Antarctic, occurring exclusively in endolithic communities of the ice-free areas of the Victoria Land, including the McMurdo Dry Valleys, the coldest and most hyper-arid desert on Earth and accounted as the Martian analog on our planet. F. endolithicus is highly successful in these inhospitable environments, the most widespread and commonly isolated species from these peculiar niches, indicating a high degree of adaptation. The nature of its extremo tolerance has not been previously studied. To investigate this, we sequenced genome of F. endolithicus CCFEE 5311 to explore gene content and genomic patterns that could be attributed to its specialization. The predicted functional potential of the genes was assigned by similarity to InterPro and CAZy domains. The genome was compared to phylogenetically close relatives which are also melanized fungi occurring in extreme environments including Friedmanniomyces simplex, Baudoinia panamericana, Acidomyces acidophilus, Hortaea thailandica and Hortaea werneckii . We tested if shared genomic traits existed among these species and hyper-extremotolerant fungus F. endolithicus . We found that some characters for stress tolerance such as meristematic growth and cold tolerance are enriched in F. endolithicus that may be triggered by the exposure to Antarctic prohibitive conditions.